2017
DOI: 10.1186/s40794-016-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antibiotic resistance profiles of Salmonella isolated from fecal matter of domestic animals and animal products in Nairobi

Abstract: Background Salmonella has significant public health implications causing food borne and zoonotic diseases in humans. Treatment of infections due to Salmonella is becoming difficult due to emergence of drug resistant strains. There is therefore need to characterize the circulating non-typhoidal Salmonella (NTS) serovars in domestic animals and animal products in Kenya as well as determine their antibiotic resistance profiles.MethodsA total of 740 fecal samples were collected from cows (n = 150), pigs (n = 182),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
4
13
3
Order By: Relevance
“…Lower rates compared to those obtained in our study (less than 1%) were reported by Smith et al [36]. In addition, high rates of resistance to nalidixic acid have been reported in Kenya (12%) [37], India (17.9% and 24.5%) [38], Romania (65.1%) [39]. However, the low rate observed in our study could be explained by the fact that fluoroquinolones are not widely used in cattle breeding in Côte d'Ivoire.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Lower rates compared to those obtained in our study (less than 1%) were reported by Smith et al [36]. In addition, high rates of resistance to nalidixic acid have been reported in Kenya (12%) [37], India (17.9% and 24.5%) [38], Romania (65.1%) [39]. However, the low rate observed in our study could be explained by the fact that fluoroquinolones are not widely used in cattle breeding in Côte d'Ivoire.…”
Section: Discussioncontrasting
confidence: 71%
“…This prevalence of 20% of Salmonella strains determined in our study is higher than that determined by Alemayehu et al [21] who reported a prevalence of 7.1%. Studies in Ethiopia (2.3%) and Nairobi (2.6%) reported lower prevalences than those obtained in this study [22,23]. Significantly lower carriage of Salmonella has been reported in cattle in Japan and Great Britain with prevalence of 0.5% and 1.4% respectively [24,25].…”
Section: Discussioncontrasting
confidence: 60%
“…The chicken are often administered antibiotics for prevention and treatment of diseases [12, 13]. Previous studies on antimicrobial resistance have revealed high resistance levels in bacterial isolates from rectal swabs of Kenyan chicken [14, 15]. However, much less has been investigated on the associated antimicrobial resistance genes.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonellae have been reported from abattoir settings in different parts of Nigeria such as Osun State, (Omololu-Aso et al, 2017); Port Harcourt, (Ire et al, 2017); Benue State, (Nseabasi-Maina et al, 2017); Sokoto, (Bagudo et al, 2014;Faleke et al, 2017). Also from other Africa regions in Nairobi, Kenya (Nyabundi et al, 2017); Kampala, Uganda (Tinega et al, 2016); Mansoura, Egypt (Sallam et al, 2014) and Modjo and Bishoftu, Ethiopia (Kuma et al, 2017). Salmonella are among organisms currently under public health surveillance for antimicrobial resistance (NARMS, 2013).…”
Section: Introductionmentioning
confidence: 99%